Enhancing SME Growth Through Online Banking Solutions: Opportunities And Challenges In The Digital Era - Fuazi Djibran (Jurnal Riset Multidisiplin Edukasi, 2025)
Small and Medium Enterprises (SMEs) play a vital role in economic development, yet they often face challenges in accessing financial resources and managing operations efficiently. The advent of online banking solutions presents significant opportunities to address these issues by offering financial inclusion, cost efficiency, improved cash flow management, and access to market insights. However, SMEs encounter barriers such as limited digital literacy, inadequate infrastructure, cybersecurity risks, and regulatory complexities in adopting these solutions. This article explores the potential of online banking to drive SME growth, analyzes success stories and regional adoption trends, and provides recommendations for stakeholders, including SMEs, online banking providers, policymakers, and financial institutions. By addressing key challenges and fostering collaboration, stakeholders can create a supportive ecosystem that enables SMEs to thrive in the digital era.